Towards optical fibre based Raman spectroscopy for the detection of surgical site infection - Thompson,AJ; Koziej,L; Williams,H; Elson,D; Yang,G (SPIE, 2016)
Surgical site infections (SSIs) are common post-surgical complications that remain significant clinical problems, as they are associated with substantial mortality and morbidity. As such, there is significant interest in the development of minimally invasive techniques that permit early detection of SSIs. To this end, we are applying a compact, clinically deployable Raman spectrometer coupled to an optical fibre probe to the study of bacteria, with the long term goal of using Raman spectroscopy to detect infection in vivo. Our system comprises a 785 nm laser diode for excitation and a commercial (Ocean Optics, Inc.) Raman spectrometer for detection. Here we discuss the design, optimisation and validation of this system, and describe our first experiences interrogating bacterial cells (Escherichia coli) in vitro. © (2016) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.